2004
DOI: 10.1023/b:biop.0000024276.03834.8d
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Thiourea and Phosphorus on Clusterbean Under Water Stress

Abstract: Effects of phosphorus and thiourea application (either alone or in combination) were studied on clusterbean (Cyamopsis tetragonoloba Taub.) plants subjected to water stress by withholding irrigation at pre-and post-flowering stages in pot culture trial. Water stress significantly decreased shoot water potential, relative water content of leaves, net photosynthetic rate, contents of total chlorophyll, starch and soluble proteins as well as nitrate reductase activity at both the growth stages. Application of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 21 publications
1
37
1
Order By: Relevance
“…They suggested that increase in the storage pool of nitrate in shoots under drought stress is related to its role as an osmoticum. Nitrate reductase is considered as an enzyme sensitive to water stress (Barathi et al 2001;Burman et al 2004) but in our investigations, imposed stress factors did not change plant turgor and water content in examined organs of cucumber (Table 1).…”
Section: Discussioncontrasting
confidence: 47%
“…They suggested that increase in the storage pool of nitrate in shoots under drought stress is related to its role as an osmoticum. Nitrate reductase is considered as an enzyme sensitive to water stress (Barathi et al 2001;Burman et al 2004) but in our investigations, imposed stress factors did not change plant turgor and water content in examined organs of cucumber (Table 1).…”
Section: Discussioncontrasting
confidence: 47%
“…Salt stress, in fact, has been reported to reduce these compounds in plants (Raza et al 2007;Daei et al 2009;Uddin et al 2011) thereby causing reduced biomass production of different plant species. Secondly, this enhancement in the biomass production in maize plants due to foliar application of mannitol and thiourea might have been due to their role in cellular osmotic adjustment (Burman et al 2004;Seckin et al 2009), because in the present study, foliar application of these organic compounds significantly enhanced the leaf RWC of maize plants that was positively associated with the enhanced plant biomass production.…”
Section: Discussionmentioning
confidence: 57%
“…As mentioned above, Roundup significantly decreased water content in roots and simultaneously increased markedly nitrate reductase activity. Literature data state that nitrate reductase is characterized by high sensitivity to water deficit and its activity rapidly falls under water stress (Barathi, et al, 2001;Burman, et al 2004). It is possible that some stress proteins protect root enzymes and their mRNA against negative influence of water deficit and directly against damage caused by Roundup.…”
Section: Discussionmentioning
confidence: 99%